Chinese ornaments on the Siti Inggil Keraton Kasepuhan building from a Religious Moderation perspective - Mukhoyyaroh; Yunus (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
This research aims to analyze the Chinese ornaments in the Siti Inggil building of the Kasepuhan Palace and the values of religious moderation. This study uses a qualitative method. Meanwhile, the approaches used are historical, anthropological, and semiotic approaches. The Chinese ornaments attached to the Siti Inggil building of the Kasepuhan palace in Cirebon align with the values of religious moderation that are growing and developing in Indonesia. Some of the ornaments on the Siti Inggil building come from cultures outside of Islam, showing the Sultan's moderate attitude and containing the values of religious moderation. First, Siti Inggil implies tolerance and accommodation towards Islamic, Hindu, and Chinese cultures within it. This means there is a willingness to understand and be ready to live with people of different religions and cultures. Second is ceramics, which implies the socio-cultural capital of religious moderation. This is because dialogue between culture and Islam has become necessary and requires good dialectics to occur to balance (tawazun) in social life in interaction with social culture